Relationship between the head teacher's instructional leadership and the school's academic achievement in the primary schools in Kuching / Jaku Nginyak @ Jukau - Nginyak @ Jukau, Jaku (2013)
This study attempted to explore the contributing instructional leadership factors among the head teachers align to their role as an instructional leader in improving the schools' academic achievement. The study was conducted in the primary schools of Kuching district. The rephrase study was conducted among teachers to gauge their perception towards their head teachers as an instructional leader and the relationship to their school's academic achievement. Currently, the academic achievement of the schools, particularly in the Primary School Assessment Examination or the "Ujian Penilaian Sekolah Rendah" (UPSR) among the schools in Kuching district is at the varied levels of achievement. In this era of educational transformation, the head teacher is regarded as the most important person in a school. The failure and success of a school in academic achievement depends on how the head teacher as an instructional leader manages the school. For the purpose of this study, 500 questionnaires were administered or sent to 63 primary schools. Only 355 (71%) respondents from 55 (87.3%) schools had responded appropriately to the questionnaires to be analysed. The instrument used in this study is an adopted and adapted model from Hallinger & Murphy (1985); that is the Principal Instructional Management Rating Scales (PIMRS). It was pilot tested to fit into the Malaysian schools' setting, particularly in the Kuching district. The analysis of the study has indicated that there were three factors namely, Practising School Goals (PSG), Enhancing Instruction (EI), and Complementing Success (CS). Besides that, the factors were also analyzed to determine its relative importance to the school's academic achievement. The findings indicated that "Complementing Success" dominated the other two factors and it was relatively important for the head teacher to practise these factors as an instructional leader. Another analysis carried out was to seek the correlation between the factors and the school's academic achievement. The result showed that the instructional leadership factors were significantly correlated to the Schools' Academic Achievement (SAA). Therefore, it is recommended that the head teachers need to play intensively the roles as instructional leaders to enhance the schools' academic achievement.